THE TYPES OF ASSESSMENT (FORMATIVE vs. SUMMATIVE, PEER vs. TEACHER FEEDBACK) AND THEIR ROLE IN PROVIDING MEANINGFUL FEEDBACK THAT IMPROVES LANGUAGE LEARNERS` PERFORMANCE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Clear and precise assessment plays a vital role in both language teaching and learning, allowing teachers and learners monitor the progress, analyze the weaknesses as well as improve needed area to achieve learning objectives and cover students` needs, expectations. In order to make the assessment process easy and effective, educators may utilize a variety of ways such as Formative and Summative one. Both of these have their own unique benefits towards language acquisition like assessment as a motivator, stimulator, reward and so on. Additionally, assessment can be in the form of oral and written format regarding teacher and learners wishes.